First invasion of Ambrostoma superbum (Thunberg, 1787) (Coleoptera, Chrysomelidae) in Western Siberia - Andrei A. Legalov; Sergei V. Reshetnikov (Acta Biologica Sibirica, 2022)
The first invasion of Ambrostoma superbum (Thunberg, 1787) (Chrysomelidae: Chrysomelinae, Doryphorini) from Novosibirsk (Novosibirskaya Oblast) is recorded. The distribution map, illustrations and redescription of this species are presented. This species causes significant damage to Ulmus pumila L.